The notion of anthropology in Kant's philosophy - Klemme H. F. (Кантовский сборник, 2010)
This article analyses different definitions, types and tasks of Kant's anthropology: Is "moral" or "practical" anthropology identical to "pragmatic" anthropology? Does anthropology aim to answer the question about the vocation of a human being? To what extent is metaphilosophy present in the Anthropology? What is the 'fundamental' transcendental anthropology? The idea of an anthroponomy remains an unsolved puzzle.